Faktor Ideasi dalam Proses Kreasi Seniman Lukis Jelekong - Uzda Nabila Shabiriani; Deny Willy Junaidy; Pindi Setiawan (Mudra Jurnal Seni Budaya, 2020)
Jelekong painters community transferred their knowledges to generations by hereditary who do not have formal art education background because unlike the creation process (formally) learned in university, Jelekong painting artists could have their own understanding of such concept. This research aims to determine the ideation factor in the creation process of Jelekong painting artists who do not have formal art education background to build an understanding of creation process in the context of hereditary painting knowledges. The creation process at early stage of the idea analyzed using verbal report method, though an associative concept network analysis of subject’s experience when drawing sketches, image analysis and factor analysis. From the data analysis results, 10 Jelekong painting artists examined in their minds when the drawing sketches process leads to harmony indicated by the distance close of houses, the object placement generally amount to two on the right and left, the different colors of distant and near objects, the ideal natural landscape with clouds, figurative shapes and other natural objects, sung the different lines to give texture, different professions, different activities, and balanced composition. When drawing sketches, the painters also considers the serenity that is indicated through a quiet atmosphere in the absence of damaged natural elements, such as drought but cozy atmosphere, painters’ memories of a cozy and quite natural atmosphere, pictures with a large space, as if there is only one house and extremely rare draw many living things. The ideation factor in the creation process of Jelekong painting artists tends to practice imitating or copying works that have been made before and really rare to find the element of novelty that causes harmony and serenity factors frequently found in each works.